Geopora ramila sp. nov. (Pezizales, Pyronemataceae) evidenced by morphological characters and phylogenetic analyses in Iran - Sheibani, Masoud; Jamali, Samad (Phytotaxa, 2020)
A new Geopora species (Pyronemataceae), Geopora ramila was described and illustrated from the soil, under or in the vicinity of Helianthemum ledifolium var. ledifolium annual plant in Fars province, Iran. Morphologically, G. ramila is similar to G. pinyonensis and G. arenicola but distinguished from both by a combination of morphological characters including, color and size of ascocarps, size and shape of ascospores, habit and associated host. The ribosomal DNA internally transcribed spacer (rDNA ITS) sequence of the new species (Acc. No. MT108930 to MT108934) showed 87.82% identity with G. pinyonensis in the BLAST search in GenBank. ITS-based phylogenetic analysis clearly supports G. ramila is a new and distinctive species lacking close relatives among described species of Geopora.